221k views
9 votes
Find the inverse of the function.
h(x)=-1/3x-5/3

User Dossani
by
5.0k points

1 Answer

10 votes

Answer:


h^(-1) (x) = 5 - 3x

Explanation:

let h(x) = y and rearrange making x the subject

y = -
(1)/(3) x -
(5)/(3) ( multiply through by 3 to clear the fractions )

3y = - x - 5 ( add 5 to both sides )

3y + 5 = - x ( multiply through by - 1 )

- 3y - 5 = x

change y back into terms of x with x =
h^(-1) (x) , that is


h^(-1) (x) = - 3x - 5

User Chris Thornton
by
5.0k points